Quinolone accumulation in Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. - McCaffrey, C (1992)
The accumulation of quinolones by Escherichia coli JF568, Pseudomonas aeruginosa PAO1, and Staphylococcus aureus ATCC 29213 was measured by a modified fluorometric assay (J. S. Chapman and N. H. Georgopapadakou, Antimicrob. Agents Chemother. 33:27-29, 1989). The quinolones examined were fleroxacin, pefloxacin, norfloxacin, difloxacin, A56620, ciprofloxacin, ofloxacin, and Ro 09-1168. In all three organisms, uptake was complete in less than 5 min and was proportional to extracellular quinolone concentrations between 2 and 50 micrograms/ml, which is consistent with simple diffusion. Washing cells with quinolone-free buffer decreased accumulation by up to 70% in E. coli and P. aeruginosa but not in S. aureus. Similarly, incubation with the uncouplers 2,4-dinitrophenol and carbonyl cyanide m-chlorophenylhydrazone increased accumulation up to fourfold in E. coli and P. aeruginosa, though not in S. aureus, suggesting endogenous, energy-dependent efflux. High quinolone hydrophobicity was generally associated with decreased accumulation in E. coli and P. aeruginosa (except in the case of pefloxacin) but was associated with increased accumulation in S. aureus (except in the case of difloxacin). Ciprofloxacin had the highest accumulation in E. coli and P. aeruginosa, while pefloxacin had the highest accumulation in S. aureus.